2015
DOI: 10.1159/000437338
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Observational Survey on the Long-Term Effect of LDL Apheresis on Drug-Resistant Nephrotic Syndrome

Abstract: Background/Aims: LDL apheresis (LDL-A) is used for drug-resistant nephrotic syndrome (NS) as an alternative therapy to induce remission by improvement of hyperlipidemia. Several clinical studies have suggested the efficacy of LDL-A for refractory NS, but the level of evidence remains insufficient. A multicenter prospective study, POLARIS (Prospective Observational Survey on the Long-Term Effects of LDL Apheresis on Drug-Resistant Nephrotic Syndrome), was conducted to evaluate its clinical efficacy with high-le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 26 publications
1
50
0
Order By: Relevance
“…Initial results demonstrated nearly 50% reductions in both total cholesterol and LDL cholesterol levels during treatment 143 . A follow-up paper 144 demonstrated complete remission in 25% of the 44 patients enrolled in the study, and reported that an additional 23% of patients had partial remission (defined as <1 g of urinary protein per day). Furthermore, a case report demonstrated the induction of remission by lipid apheresis in an adult with rituximab-resistant nephrotic syndrome 145 .…”
Section: Treatment Of Dyslipidaemiamentioning
confidence: 99%
“…Initial results demonstrated nearly 50% reductions in both total cholesterol and LDL cholesterol levels during treatment 143 . A follow-up paper 144 demonstrated complete remission in 25% of the 44 patients enrolled in the study, and reported that an additional 23% of patients had partial remission (defined as <1 g of urinary protein per day). Furthermore, a case report demonstrated the induction of remission by lipid apheresis in an adult with rituximab-resistant nephrotic syndrome 145 .…”
Section: Treatment Of Dyslipidaemiamentioning
confidence: 99%
“…A recent single arm observational study (POLARIS; N = 44) found that low‐density lipoprotein apheresis (LDL‐A) was able to ameliorate nephrotic syndrome in half of patients who were found to be drug resistant. Those patients who experienced disease remission continued to have a favorable outcome after 2 years of follow up . In this study, decreased urinary protein levels after treatment was most significantly correlated with a favorable 2‐year outcome.…”
Section: Introductionmentioning
confidence: 50%
“…In addition, the POLARIS study revealed that the change in the urinary protein after LDL-A may be a significant predictor of the outcome (2). …”
Section: Discussionmentioning
confidence: 99%